Stability of tunnel face in unsaturated sand possessing apparent cohesion: A micro-macro analytical approach - He, Junzuo; Liao, Shaoming; Liu, Mengbo; Motoi, Iwanami; Xiao, Junhua (Soils and Foundations, 2023)
Although the stability of tunnel face in the dry and saturated sandy ground is widely studied, the unsaturated sandy ground which possesses apparent cohesion is more common in engineering. For remedying this deficiency, the theoretical association between apparent cohesion and the saturation degree is firstly established in microscopic prospective. Then, the formation mechanism of the self-stabilized arch and the limit support pressure (LSP) of the tunnel face are derived by incorporating apparent cohesion into the macroscopic limit equilibrium analysis of the multi-arches model. Subsequently, the validities of the proposed approach in estimating apparent cohesion, loosening zone height and LSP are well confirmed (the average error rates of LSP are within 12 %) via comparisons with direct shear tests, model tests and other existing methods. Finally, as revealed by the parametric discussion, under the effect of apparent cohesion, LSP is negatively correlated with compactness, internal friction angle, and contact angle while decreases firstly (to a minimum value of 0.09γD ∼ 0.15γD) and then increase with the rise of saturation degree. Besides, the LSP has a parabolic distribution along the depth with its peak value emerges between 0.3D and 0.45D.